(untitled) - Malherbe, Christiaan Johannes

Control analysis of mixed populations of gluconobacter oxydans and saccharomyces cerevisiae (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Biochemistry))--University of Stellenbosch, 2010.